The ethnoprimatology of the Maijuna of the Peruvian Amazon and implications for primate conservation - Carla Mere Roncal; Mark Bowler; Michael P Gilmore (BMC, 2018)
Abstract Background In Amazonia, primates are not only an important food source but they also hold significant cultural and symbolic value for many indigenous groups. We document the relationship between primates and community members of the Maijuna indigenous community of Sucusari in the Peruvian Amazon and describe how ethnoprimatological studies provide a better understanding of the significance of primates in people's lives. Additionally, we explore how ethnoprimatological studies can help inform and enhance primate conservation initiatives. Methods Semi-structured interviews were conducted with 50 residents of the community of Sucusari to assess the classification, cultural significance and traditional uses, beliefs, ceremonies and stories of primates within the Sucusari River basin. Results Primates play an important role in the lives of individuals in the Sucusari community. They are distinguished by their arboreal lifestyle, and among the 11 species reported in the area, seven (Lagothrix lagotricha, Alouatta seniculus, Pithecia monachus, Callicebus spp., Saimiri sciureus, Leontocebus nigricollis) are highly recognized and culturally salient. Primates are used as food, medicine, pets, domestic tools and in the production of handicrafts. They are primarily hunted for local consumption, with larger primates such as L. lagotricha being preferred. Lagothrix lagotricha was also the most commonly reported pet species and the only observed pet primate in the community during surveys. Maijuna traditional beliefs include ancestral dietary taboos for A. seniculus, which are referred to as sorcerer monkeys, but this taboo is no longer fully adhered to. Maijuna traditional stories associated with primates describe the origin of primates found in Sucusari. Conclusion Primates are embedded in the intricate sociocultural system of the community of Sucusari. Better understanding the relationship between primates and people can help to focus conservation efforts on primate species of particularly high sociocultural importance as well as ecological value, such as L. lagotricha. We highly recommend the inclusion of ethnoprimatological studies into primate conservation initiatives to accomplish more effective conservation planning, ultimately integrating the goals of biodiversity conservation with the cultural and economic needs of indigenous and local communities.